Morphological diagnoses of higher taxa in Ophiuroidea (Echinodermata) in support of a new classification - O'Hara, Timothy D.; Stöhr, Sabine; Hugall, Andrew F.; Thuy, Ben; Martynov, Alexander (European Journal of Taxonomy, 2018)
A new classification of Ophiuroidea, considering family rank and above, is presented. The new family and superfamily taxa in O’Hara et al. (2017) were proposed to ensure a better readability of the new phylogeny but are unavailable under the provisions of the ICZN. Here, the morphological diagnoses to all 33 families and five superfamilies are provided. Ten new families, Ophiosphalmidae fam. nov., Ophiomusaidae fam. nov., Ophiocamacidae fam. nov., Ophiopteridae fam. nov., Clarkcomidae fam. nov., Ophiopezidae fam. nov., Ophiernidae fam. nov., Amphilimnidae fam. nov., Ophiothamnidae fam. nov. and Ophiopholidae fam. nov., are described. The family Ophiobyrsidae Matsumoto, 1915, not yet discovered in the previous publication, is added, based on new molecular data. A new phylogenetic reconstruction is presented. Definitions of difficult-to-apply morphological characters are given.